EFEKTIVITAS METODE COOPERATIVE LEARNING PADA HASIL BELAJAR BAHASA INDONESIA MATERI PUISI SISWA KELAS X SMA AL-IKHLAS KOTA BEKASI - Luluk Setyowati; Sigit Widiyarto; Aster Pujaning Ati; Lengsi Manurung; Loecita Sandiar; Nana Suyana (Jurnal Bahasa Indonesia Prima (BIP), 2023)
Learning the Indonesian language and literature still needs to be optimal. Learning needs to get the attention of teachers and educational observers. Good learning makes students happy and comfortable and gets optimal learning results. This study aimed to determine the effectiveness of cooperative learning in class X high school students with poetry material. The method used is an experimental method with the type of pretest-posttest. Respondents who participated in the study were 42 students. Research activities were carried out from January to March 2019. The study's results stated an increase of 4.7464 when students used cooperative learning. The learning process begins with forming groups and interactions between students and teachers. This method can provide added value before and after using the method.